2005
DOI: 10.1080/09670260500254743
|View full text |Cite
|
Sign up to set email alerts
|

A molecular re-examination of speciation in the intertidal red algaMastocarpus stellatus(Gigartinales, Rhodophyta) in Europe

Abstract: Mastocarpus stellatus is a common intertidal red alga in the north Atlantic. Previous work showed that the species was divided into at least two breeding groups in the northeastern Atlantic, a northern one (absent in Spain and Portugal) and a southern one, which were almost completely inter-sterile. It also showed that, in laboratory culture, at least two types of life history were evident in this species (a sexual one and a 'direct' one). The distribution of these life histories appeared to have a north-south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Moreover, these Vancouver Island populations are odd because specimens with ITS of Mastocarpus agardhii have organelle sequences from other species as noted above. (Zuccarello et al 2005 also observed mixed genotypes in European Mastocarpus, with asexual thalli having the plastid haplotype of the northern breeding group and the mitochondrial haplotype of the southern breeding group.) The occurrence of Mastocarpus latissimus in Chile, with little genetic differentiation from some California specimens, also raises the possibility of modern, anthropogenic dispersal.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, these Vancouver Island populations are odd because specimens with ITS of Mastocarpus agardhii have organelle sequences from other species as noted above. (Zuccarello et al 2005 also observed mixed genotypes in European Mastocarpus, with asexual thalli having the plastid haplotype of the northern breeding group and the mitochondrial haplotype of the southern breeding group.) The occurrence of Mastocarpus latissimus in Chile, with little genetic differentiation from some California specimens, also raises the possibility of modern, anthropogenic dispersal.…”
Section: Discussionmentioning
confidence: 79%
“…Discrepancies between molecular markers have uncovered cases of putative hybridization between different species (e.g., red algae: Zuccarello et al. 2005, Brodie and Zuccarello 2006, Niwa et al.…”
mentioning
confidence: 99%
“…2009, Destombe et al. 2010), and the resulting offspring is often sterile or reproduces exclusively apomictically (Zuccarello et al. 2005, Kamiya and West 2008).…”
mentioning
confidence: 99%